COMPARISON OF APPROACHES TO REDUCE AND PREVENT FROM CHILDREN OBESITY WITHIN THE CONTEXT OF UK AND POLAND - Parlińska, Agnieszka; Rembielak, Grażyna (Acta Scientiarum Polonorum. Oeconomia, 2014)
The problem of obesity relates to adults as well as children and teenagers. In the last decade it has become a crucial public health problem all over the world. It has been acknowledged by various organisations and bodies globally, nationally, and regionally, such as for example: World Health Organisation, European Union Commission, national governments, National Health Service, and other non-governmental institutions, as well as media. The paper focuses on two case studies on children obesity prevention and reduction activities in the example of two selected European countries: the United Kingdom, and Poland. Findings for the analysis were obtained from variety of sources such as: various literature, reports of Organisation of Economic Cooperation and Development (OECD), World Health Organisation (WHO), National Health Service (NHS) - National Obesity Observatory, British Broadcasting Corporation (BBC), Chief Sanitary Inspectorate (Główny Inspektorat Sanitarny - GIS). The results highlight the significance of understanding the current situation regarding obesity and the future trends of this problem, emphasising that investment in programmes and activities to fight it and prevent from it will bring benefits to countries and societies from an individual perspective as well as globally.